THE EFFECTIVENESS OF USING CARTOON MOVIE TOWARD STUDENTS’ VOCABULARY MASTERY - Sutrisno Sadji Evenddy; Delsa Miranty; Risa Rahmawati (Jurnal Bebasan, 2018)
The objective of the research was to find out the effectiveness of using cartoon movie toward students’ vocabulary mastery at the seventh grade of SMPN2 Kota Serang. The researcher used quantitative research by applying true experimental design for conducting the research. The population of this research was the seventh grade students of SMPN 2 Kota Serang. The sample of this research was the students of VII A as experimental class and VII B as control class. Each class consisted of 37 students. The classes were chosen by cluster random sampling from ten classes. In collecting the data, the researcher conducted pre-test and post-test. Pre-test was given to the classes before treatment. Then treatment was given only to experimental class for two meetings. Post-test was given to the classes after treatment. In analyzing the data, the researcher used T-test. The result of the calculation showed that is tcount (20.2) is higher than ttable (1.99). It means that null hypothesis (Ho) is rejected and alterative hypothesis (Ha) is accepted. Therefore, cartoon movie is effective on the students’ vocabulary mastery at the seventh grade of SMPN 2 Kota Serang and one of the media which is can help the students in solving their problem in learning English vocabulary. In addition, cartoon movie can make the students enthusiastic, interested, and enjoy in learning English vocabulary.